Faktor-faktor yang Mempengaruhi Pola Makan Siswa Sekolah Dasar di Kabupaten Banyumas - Katri Andini Surijati; Pramesthi Widya Hapsari; Windri Lesmana Rubai (Program Studi Gizi, Universitas Bumigora, 2021)
Good nutrition during childhood is necessary for growth and development, health, well-being, and prevention of obesity and several other chronic diseases. Children's eating practices can also have short- and long-term health consequences, increase the risk of some non-communicable diseases (PTM), and contribute significantly to the burden of preventable diseases and premature death. School-age children have the characteristics of a lot of physical activity so that they require sufficient energy to meet their activity and growth needs. In general, the factors that influence diet are physical activity, education, knowledge of nutrition, work status and family socioeconomic status. This study aims to see the factors that influence the diet of elementary school children in Banyumas Regency. Data collection using Google Forms to prevent the transmission of the Covid-19 virus. The data were analyzed using multiple linear regression analysis to determine the factors that influence the diet of school children. The results showed that physical activity (0.045), age (0.27), mother’s education (0.37), knowledge of nutrition (0.34), employment status (0.12), eating patterns (0.34) and family income (0.25) affects food consumption pattern of children with a level of confidence, while gender does not affect the diet of school children. This study concludes that mother’s factors greatly affect the dietary consumption patterns of school children.